2024
DOI: 10.31223/x5th5x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of climate change on average and peak demand for heating and cooling across the contiguous United States

Abstract: While most electricity systems are designed to handle peak demand during summer months, pathways to deep decarbonization generally electrify building heating, thus increasing electricity demand during winter. A key question is how climate variability and change will affect peak heating and cooling demand in an electrified future. We conduct a spatially explicit analysis of trends in temperature-based proxies of electricity demand over the past 70 years. Average annual demand for heating (cooling) decreases (in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly, a comparison of 1996-2005 weather data in Texas with downscaled projections under RCP 8.5 for 2041-2050 revealed that under this high-emissions scenario, net demand could increase by up to 6% and thermal deratings during peak hours could increase by 40% (Craig et al, 2020). A retrospective and temperature-based analysis observed consistent increases in summer average and peak cooling demand across the continental United States (Amonkar et al, 2023). While warmer winters reduce total electricity demand during winters, researchers found that the likelihood and severity of extreme cold temperatures in the mid-latitudes, which are particularly consequential for electricity systems, are unlikely to decrease for several decades (Doss-Gollin et al, 2021;Cohen et al, 2020).…”
Section: Electricity Demandmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, a comparison of 1996-2005 weather data in Texas with downscaled projections under RCP 8.5 for 2041-2050 revealed that under this high-emissions scenario, net demand could increase by up to 6% and thermal deratings during peak hours could increase by 40% (Craig et al, 2020). A retrospective and temperature-based analysis observed consistent increases in summer average and peak cooling demand across the continental United States (Amonkar et al, 2023). While warmer winters reduce total electricity demand during winters, researchers found that the likelihood and severity of extreme cold temperatures in the mid-latitudes, which are particularly consequential for electricity systems, are unlikely to decrease for several decades (Doss-Gollin et al, 2021;Cohen et al, 2020).…”
Section: Electricity Demandmentioning
confidence: 92%
“…A particular challenge is that in many regions, the interannual variability of peak heating demand (i.e., winter temperature extremes) is substantially larger than peak cooling demands (i.e., summer temperature extremes). As electrification of building heating continues, grids must prepare for rare and variable winter peaks rather than for frequent and more predictable summer peaks (Amonkar et al, 2023;Doss-Gollin et al, 2021).…”
Section: Technological and Social Factors Contributing To Climatementioning
confidence: 99%
See 1 more Smart Citation